2019
DOI: 10.12659/msm.920459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eating Breakfast on Cognitive Development of Elementary and Middle School Students: An Empirical Study Using Large-Scale Provincial Survey Data

Abstract: BackgroundIn existing research on the importance of student breakfast, few studies have focused on the impact of breakfast on student cognitive development. Further, empirical research in this field is mostly based correlation analysis, in which it is difficult to control the influence of selection bias on the analysis results.Material/MethodsHere, we used student academic performance, based on the academic quality monitoring data of Jiangsu basic education students, as a proxy variable for cognitive developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…Furthermore, no evidence of differences according to their nutritional status was established. In this sense, several studies showed that skipping breakfast impacts the children and adolescents’ cognitive and academic achievement, negatively impairing their problem-solving ability, attention, and episodic memory in the morning [ 12 , 13 , 42 ]. However, this detrimental cognitive effect was not observed in children (8–10 years) who regularly consumed breakfast and skipped it once [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, no evidence of differences according to their nutritional status was established. In this sense, several studies showed that skipping breakfast impacts the children and adolescents’ cognitive and academic achievement, negatively impairing their problem-solving ability, attention, and episodic memory in the morning [ 12 , 13 , 42 ]. However, this detrimental cognitive effect was not observed in children (8–10 years) who regularly consumed breakfast and skipped it once [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these relevant aspects, it is also crucial to consider the adolescents’ social context and familial support, because most “breakfast skippers” have unfavorable socio-economic backgrounds [ 12 , 45 ]. Social factors have been related to worse food quality and physical inactivity, among others, influencing a higher rate of overweight/obesity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we firstly used large-scale testing and survey data from the monitoring of the academic quality of students in basic education in Jiangsu Province to study the potential role of breakfast in students' cognitive development. Our finding indicated that regularly eating breakfast significantly promoted students' cognitive development (Yao et al, 2019). Based on this finding, we move on to question between eating breakfast and attending tutoring, which one is more effective in improving students' performance?…”
Section: Introductionmentioning
confidence: 70%
“…Children and adolescents who regularly consume breakfast more likely have a good diet quality [ 13 , 14 , 15 , 16 , 17 ]. Moreover, having breakfast has also been associated with positive effects on students’ cognitive development and better school performance in children [ 18 , 19 , 20 , 21 ]. However, breakfast is the meal that is most often skipped by children and adolescents [ 22 ].…”
Section: Introductionmentioning
confidence: 99%